Methane and microbial dynamics in the Gulf of Mexico water column - Rakowski, Chrisoulla; Magen, Cedric; Bosman, Samantha; Gillies, Lauren; Rogers, Kelsey; Chanton, Jeff; Mason, Olivia U. (Frontiers in Marine Science, 2015)
In contrast to other oligotrophic water bodies the Gulf of Mexico (GOM) hosts an abundance of hydrocarbon seeps, which likely influences the microbial assemblages it hosts particularly regarding the availability of labile carbon in the aphotic GOM. The aphotic zone receives direct injection of seep methane (CH4), but CH4 from an unknown source has been reported at supersaturated concentrations relative to the atmosphere in the GOM photic zone. Here we used iTag sequencing of 16S rRNA genes to characterize GOM microbial communities and to relate changes in microbial community structure to the properties inherent to their oceanic province-seafloor to the photic zone, seep and non-seep. Along this trajectory water column communities were distinct in the euphotic zone compared to the mesopelagic and deep-sea. In the euphotic zone the relative abundance of a cyanobacterial species (Prochlorococcus) was significantly correlated with both CH4 and chlorophyll a concentrations and was abundant in some deep-chlorophyll maximum (DCM) samples. The relative abundance of microorganisms related to known hydrocarbon degraders were also significantly correlated with CH4 in the euphotic zone, but no canonical methanotrophs were observed. In the mesopelagic to the seafloor canonical methanotrophs were identified, but only a Marine Group II Euryarchaeota was significantly correlated with CH4. Overall, depth and the associated environmental conditions were the primary drivers in structuring microbial communities over the GOM water column. Further, CH4 concentrations and relative microbial abundances covaried significantly from the seafloor to the photic zone in the GOM. The lack of a significant relationship between canonical methanotrophs and CH4 in the aphotic zone, even when sampling at seep sites, may suggest methane-oxidation by unknown microorganisms. Similarly their absence in the CH4 maximum and DCM suggested that CH4 is either oxidized by unrecognized methanotrophs or escapes the CH4 biofilter and fluxes to the atmosphere.